Modern Ukrainian TV series: challenges of the global multimedia market - Priadko, Oleksandr; Kostiuk, Nataliia; Cherkasova, Nataliia; Moussienko, Oksana; Levchenko, Olena (Linguistics and Culture Review, 2021)
The aim of the paper is to study the modern Ukrainian TV industry in comparison with foreign examples and to formulate the requirements that a Ukrainian TV series must meet in order to enter the global market. The following methods were used during the work: descriptive method and typology, comparative analysis, and synthesis, each of these methods corresponds to one of the three stages of the study. This contributed to the achievement of the following results: the features of the modern TV series were characterised and its main types were identified; the domestic and foreign markets of multimedia products were studied and their common features and differences were revealed; formulated requirements that the Ukrainian TV series must meet in order to enter the global market. The scientific novelty of the paper lies in the detailed study of modern formats and descriptions of the general features of TV series, which allowed to perform the classification and thoroughly analyse each of the genres and types of TV series. The practical significance lies in the fact that the developed criteria for a modern series should be used as a recommendation when creating a multi-episode project.